Pengaruh Electronic Service Quality terhadap Repurchase Intention yang Dimoderasi Oleh Kepercayaan Konsumen - Rissa Arvianti; Hendrati Dwi Mulyaningsih; Yudha Dwi Nugraha (UNISBA Press, 2023)
Abstract. This research focuses on the variables of e-service quality, repurchase intention, and consumer trust. The purpose of this study is to determine the relationship between e-service quality and repurchase intention and the role of consumer trust as a moderating variable on Video-on-Demand Netflix. The method used in this study is a survey method with a questionnaire instrument as the data collection technique. The object of this research is official Netflix users who are domiciled in Bandung, totaling 200 people based on the sampling criteria. The sampling technique in this study used purposive sampling. There are two hypotheses in this study. To test the hypothesis, the techniques used are simple regression analysis and MRA (Moderated Regression Analysis). The results of this study indicate that there is a positive and significant effect of e-service quality on repurchase intention on Video-on-Demand Netflix. Furthermore, consumer trust strengthens the relationship between e-service quality and repurchase intention on Video-on-Demand Netflix. Abstrak. Penelitian ini berfokus kepada variabel e-service quality, repurchase intention, dan kepercayaan konsumen. Tujuan dari penelitian ini ialah untuk mengetahui hubungan antara e-service quality dan repurchase intention serta peran kepercayaan konsumen sebagai variabel moderasi pada Video-on-Demand Netflix. Metode yang digunakan pada penelitian ini ialah metode survei dengan instrumen kuesioner sebagai teknik pengumpulan datanya. Objek penelitian ini ialah pengguna Netflix resmi yang berdomisili di Bandung berjumlah 200 orang berdasarkan kriteria sampling. Teknik sampling dalam penelitian ini menggunakan purposive sampling. Terdapat dua hipotesis yang ada pada penelitian ini. Untuk menguji hipotesis, teknik yang digunakan yaitu analisis regresi sederhana dan MRA (Moderated Regression Analysis). Hasil dari penelitian ini menunjukkan bahwa terdapat pengaruh positif dan signifikan antara e-service quality terhadap repurchase intention pada Video-on-Demand Netflix. Selanjutnya, kepercayaan konsumen memperkuat hubungan antara e-service quality terhadap repurchase intention pada Video-on-Demand Netflix.